2021
DOI: 10.1186/s12888-021-03405-w
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems in children with autism spectrum disorder: a multicenter survey

Abstract: Background High prevalence of sleep problems have been reported in children with Autism Spectrum Disorder (ASD). This study aims to investigate the sleep conditions of ASD children in China, and explore the relationship between the common sleep problems and core symptoms and developmental levels. Methods Using a cross-sectional design, we included 2 to 7-year-old children from 13 cities in China: 1310 with ASD and 1158 with typically-developing (TD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 64 publications
4
33
1
1
Order By: Relevance
“…Consistent with previous studies [ 39 , 74 ], we also found that the severity of sleep disturbances, as indicated by the CSHQ total score at the baseline, correlated with a younger age and with the severity of the autistic core symptoms. Most of the participants in our cohort had severe autistic symptoms (78.7% had a comparison score of 8–10 in the ADOS-2).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies [ 39 , 74 ], we also found that the severity of sleep disturbances, as indicated by the CSHQ total score at the baseline, correlated with a younger age and with the severity of the autistic core symptoms. Most of the participants in our cohort had severe autistic symptoms (78.7% had a comparison score of 8–10 in the ADOS-2).…”
Section: Discussionsupporting
confidence: 92%
“…Most of the participants in our cohort had severe autistic symptoms (78.7% had a comparison score of 8–10 in the ADOS-2). This might explain the higher rate of participants (86%) who screened positive for sleep disturbances, compared to a rate of approximately 70% that was reported in a US registry study [ 74 ] and in a Chinese multicenter survey [ 39 ].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Research on animals and on typically developing children demonstrated that sleep deprivation may lead to impairments of adequate synaptic development and brain maturation ( 24 , 25 ); therefore, some authors have speculated that sleep dysfunction in children with ASD could actively cause disorders in synaptic function, potentially creating a maladaptive feed-forward loop of sleep disruption and neural anomalies ( 24 , 25 ). Furthermore, less sleeping time and worse quality of sleep may affect adaptive behavior (e.g., hygiene, eating, toileting…), cognition, attention, memory, learning ( 26 30 ) and executive functioning ( 31 ), and increase internalizing and externalizing problems, as depression, anxiety, self-injury, oppositional behavior, irritability, physical aggression ( 24 , 32 35 ). Sleep problems may also exacerbate the core symptom severity of ASD: poor sleepers were reported to show more restricted and stereotyped behaviors, more severe social skills deficits ( 2 , 26 , 36 40 ) and communication problems ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, less sleeping time and worse quality of sleep may affect adaptive behavior (e.g., hygiene, eating, toileting…), cognition, attention, memory, learning ( 26 30 ) and executive functioning ( 31 ), and increase internalizing and externalizing problems, as depression, anxiety, self-injury, oppositional behavior, irritability, physical aggression ( 24 , 32 35 ). Sleep problems may also exacerbate the core symptom severity of ASD: poor sleepers were reported to show more restricted and stereotyped behaviors, more severe social skills deficits ( 2 , 26 , 36 40 ) and communication problems ( 41 ). However, it is still unclear what daytime implications of sleep disorder are and the direction of their relationship.…”
Section: Introductionmentioning
confidence: 99%